Rekomendy Sebagai Website Rekomendasi Outfit Generasi Z - Suwarto; Nani Septiana; Farid Abdullah (Jurnal Manajemen DIVERSIFIKASI, 2026)
This research was aimed to develop a recommendation website which was developed as a fashion recommendation website for gen z. We found out that the increasing selection of fashion products in e-commerce, making Gen Z confused to choose the product that suits him and also confused to choose the right store. In our website we provide several interesting features, in addition to recommendations we also provide cashback on every purchase and also a real video display which will later be directed to e-commerce, for now we are still collaborating with Shopee, but in the future we expand into other e-commerce as well. The type of research used in this study was to use qualitative research methods. More precisely, descriptive qualitative which aimed to make rekomendy a platform for fashion product recommendations for gen z. Furthermore, the researcher himself was the researcher, who play the role of CEO of the recommendation. The data sources we got from two things, namely; primary, which was sourced directly from the recommendation platform, and secondary, which was sourced from data collected directly by researchers. The data collection technique itself uses several techniques, including; Observation is direct observation of the research object, interviews directed to look for information from 27 random people, and documentation sources from previous research. The results of the study showed that recommendations can be a solution for Gen Z in finding fashion products online. Judging from the interviews conducted that 26 out of 27 people need recommendations to be a recommendation platform and also they really like the features contained in this website.